Vyāptipañcakam - Jagadīśatarkālaṅkāra ca. 2. Hälfte 17. Jh. (Vidyābhavana Prācyavidyā granthamālā 229, 2010)
Sub-commentary on Anumānakhaṇḍa in the Tattvacintāmaṇi, 13th century basic treatise on Navya-Nyāya philosophy; portion dealing with definition of invariable concomitance (vyāpti); includes Vyāptipañcakarahasya of Mathurānātha Tarkavāgīśa, 1600-1675